IMPLEMENTASI MODEL PEMBELAJARAN TGT (TEAMS GAMES TOURNAMENT) UNTUK MENINGKATKAN KETERAMPILAN KERJASAMA SISWA KELAS V SDN TULUSREJO - Dwi Purwitasari, Ervina; Nurhidayati; Rizkia Pangestika, Rintis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to 1) Describe the steps of implementing the TGT (Teams Games Tournament) learning model to improve the cooperation skills of fifth grade students of Tulusrejo Elementary School, 2) Determine the improvement of cooperation skills of fifth grade students of Tulusrejo Elementary School through the TGT (Teams Games Tournament) learning model. The study used Classroom Action Research (CAR) which consists of 2 cycles. Each cycle has 2 meetings. The research subjects were 16 fifth grade students of Tulusrejo Elementary School consisting of 8 boys and 8 girls. The data collection methods used were interviews, observation and documentation. Implementation of the TGT (Teams Games Tournament) learning model with 5 stages, namely 1) Class Presentation, 2) Group Learning, 3) Games, 4) Competitions, 5) Awards. The results of the research observations are as follows: learning using the TGT (Teams Games Tournament) learning model is very suitable to be applied in Elementary Schools because the percentage of students' cooperation skills at the pre-cycle stage is 31%, cycle I becomes 44% at meeting 1 and 50% at meeting 2. Then in cycle II it increases to 69% at meeting 1 and increases significantly again to 88% meeting the specified classical completeness of 80%. From the results of the implementation of the TGT (Teams Games Tournament) learning model, it can be considered effective in improving students' cooperation skills. So this model can be used as an effective alternative strategy to improve students' cooperation skills in Elementary Schools.